A Study of the Factors That Drive Customer Retention in the E-commerce Industry: Basis for Marketing Strategies: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The e-commerce industry has been greatly impacted by the pandemic, and the number ofonline businesses has increased, where online shopping has become a trend for consumers.For customers, product information like price, product quality, place/medium, and promotionsare very important and should be transparent as they affect their buying choices. Onlinebusinesses are competing for customers in a wide market like never before. Customerretention gained increased value in e-commerce. Generally, it is recognized that there is apositive relationship between customer retention and profitability, as customer retentionallows a corporation to boost profitability and revenue by constantly purchasing a product froman online store.The findings of the study revealed that the employed and unemployed group of respondentsstrongly agree that price, product quality, place/medium, and promotions influence customersbuying behavior and affect customer retention. Moreover, the results of the study revealedthat there is no significant difference between the cited variables. The main problemsencountered as to the listed variables were overpricing, product quality being far from thecustomer’s perceived value, errors in websites, and defective freebies.This study proposed to improve the rate of customer retention by having a strong foundation ofmarketing strategies, as it can be seen as a big factor that affects the business's longevity inthe industry.
Keywords: Business